A Critical Study of Sorat e Mani, Mani e Sorat - Alvi, Qamar Abbas; Sahar, Nazia; Saddique (sourcecoder, 2024)
Sorat e Mani, Mani e Sorat is a book compiled by Junaid Amjad about famous poet Majid Amjad. Majid Amjad is a famous poet of 20th century, he was born in 1914(in Jhang) and died in 1974. 2014 was celebrated as Majid Amjad’s century; in 2014 many books were written by famous authors, Junaid Amjad also compiled Sorat e Mani, Mani e Sorat. This writing is a critical study of Sorat e Mani, Mani e sorat